2012
DOI: 10.1152/ajpheart.00663.2011
|View full text |Cite
|
Sign up to set email alerts
|

Heart angiotensin II-induced cardiomyocyte hypertrophy suppresses coronary angiogenesis and progresses diabetic cardiomyopathy

Abstract: Heart angiotensin II-induced cardiomyocyte hypertrophy suppresses coronary angiogenesis and progresses diabetic cardiomyopathy. Am J Physiol Heart Circ Physiol 302: H1871-H1883, 2012. First published March 2, 2012; doi:10.1152/ajpheart.00663.2011.-To examine whether and how heart ANG II influences the coordination between cardiomyocyte hypertrophy and coronary angiogenesis and contributes to the pathogenesis of diabetic cardiomyopathy, we used Spontaneously Diabetic Torii (SDT) rats treated without and with ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…33 , 34 VEGFR-2 is a critical factor in hypertrophic growth of cardiomyocytes. 35 , 36 We found that pioglitazone directly targeted VEGFR-2 and inhibited phospho-VEGFR-2 expression, suggesting that pioglitazone induces cardiomyocyte apoptosis and inhibits cardiomyocyte hypertrophy in neonatal rats by inhibiting VEGFR-2 signaling. Downstream PI3K/Akt signaling pathway also participates in survival and hypertrophy of these cells by inhibiting P53-dependent pathways and activating mTOR-dependent pathways, respectively.…”
Section: Discussionmentioning
confidence: 77%
“…33 , 34 VEGFR-2 is a critical factor in hypertrophic growth of cardiomyocytes. 35 , 36 We found that pioglitazone directly targeted VEGFR-2 and inhibited phospho-VEGFR-2 expression, suggesting that pioglitazone induces cardiomyocyte apoptosis and inhibits cardiomyocyte hypertrophy in neonatal rats by inhibiting VEGFR-2 signaling. Downstream PI3K/Akt signaling pathway also participates in survival and hypertrophy of these cells by inhibiting P53-dependent pathways and activating mTOR-dependent pathways, respectively.…”
Section: Discussionmentioning
confidence: 77%
“…Hypertrophic cardiomyopathy can be caused by any disease that increases cardiac afterload and volume overload, some myocardiotoxic drugs, and certain primary genetic disorders of the myocardium (Senni et al, 1998;Roura and Bayes-Genis, 2009;Masuda et al, 2012;Maron et al, 2014;Modesto and Sengupta, 2014;Patel et al, 2015). Without appropriate treatment, hypertrophic cardiomyopathy commonly develops into dilated cardiomyopathy, and ultimately decompensated heart failure (Senni et al, 1998;Roura and Bayes-Genis, 2009;Masuda et al, 2012;Patel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Without appropriate treatment, hypertrophic cardiomyopathy commonly develops into dilated cardiomyopathy, and ultimately decompensated heart failure (Senni et al, 1998;Roura and Bayes-Genis, 2009;Masuda et al, 2012;Patel et al, 2015). Doxorubicin (DOX) is used to treat a variety of human neoplasms; however, its usage is limited because of its cardiotoxicity (Blum and Carter, 1974;Von Hoff et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…In fluorescein fundus angiography, fluorescein leakage in SDT rats was decreased by telmisartan, suggesting that the ARB may inhibit the development of proliferative retinopathy in SDT rats [58]. It has also been reported that ARBs (candesartan and olmesartan) improved coronary angiogenesis, cardiomyocyte fibrosis, and hypertrophy associated with the progression of diabetes in SDT rats [59, 60]. In addition, candesartan decreased the pentosidine, a biomarker for AGE, content in the lens/vitreous body in SDT rats at 44 weeks of age, and immunohistologically, it inhibited the accumulation of pentosidine in the retinal vascular wall and decreased retinal VEGF mRNA expression [61].…”
Section: Application To Treatmentmentioning
confidence: 99%